2002
DOI: 10.1080/08035250252833950
|View full text |Cite
|
Sign up to set email alerts
|

Coeliac disease in children and adolescents with type 1 diabetes: a study of growth, glycaemic control, and experiences of families

Abstract: Coeliac disease is rarely associated with signs of malabsorption in children and adolescents with type I diabetes. Introduction of a gluten-free diet may be associated with excess weight gain. We recommend intensified follow-up for these subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 0 publications
1
18
1
2
Order By: Relevance
“…Many centers already advocate routine screening for CD in children with T1DM, but the appropriate interval between reexamination is unclear. Some have supported screening at diagnosis and then annually (6, 8, 16), others recommend screening at diagnosis of T1DM and then after 1, 3, and 5 yr (32). However, the conclusion based on our results is that children with T1DM should be screened for CD at the onset of T1DM and annually, at least for 2 yr.…”
Section: Discussionmentioning
confidence: 73%
“…Many centers already advocate routine screening for CD in children with T1DM, but the appropriate interval between reexamination is unclear. Some have supported screening at diagnosis and then annually (6, 8, 16), others recommend screening at diagnosis of T1DM and then after 1, 3, and 5 yr (32). However, the conclusion based on our results is that children with T1DM should be screened for CD at the onset of T1DM and annually, at least for 2 yr.…”
Section: Discussionmentioning
confidence: 73%
“…In recent years various studies have been published on the effects of GFD on metabolic control and growth in children with CD and T1D. Westman et al showed no difference in growth parameters while others demonstrated a non‐significant increase in BMI standard deviation scores (SDS), reduction in glycosylated haemoglobin (HbA1c), and an increase in weight for height (5–7). The present study reviews the short‐term clinical and metabolic effects of a GFD in a group of children with T1D and confirmed CD.…”
mentioning
confidence: 78%
“…In contrast, the argument against early GFD includes difficulty in handling the dietary, lifestyle, and medication management changes inherent in the care of children with both T1D and CD and lack of clear benefit in asymptomatic children 23. In children with T1D, those with evidence of symptomatic CD benefit from GFD 4,24; in asymptomatic cases the demonstrated benefit is limited to weight gain and BMD changes 25,8,5,26. In any case, adherence to GFD by children with T1D is only about 50% 4,27,28,29,30.…”
Section: Discussionmentioning
confidence: 99%